PERAN KONSULTAN PAJAK DALAM PENYUSUNAN LAPORAN KEUANGAN TERHADAP EFEKTIVITAS PERENCANAAN PAJAK - Faysi, Rizky Salman Al; Widodo, Condro (Jurnal Riset Ilmu Akuntansi, 2026)
This study aims to examine the role of tax consultants in the preparation of financial statements and their impact on the effectiveness of tax planning. Effective tax planning strategies require accurate and systematic financial records, as these serve as the foundation for legally minimizing tax burdens and ensuring compliance. Using a descriptive qualitative approach, this research collected data through in-depth interviews with tax consultants and an analysis of financial documents, tax planning reports, and consultation records. The findings indicate that tax consultants play a critical role not only in advising on tax strategies but also in ensuring that financial data is recorded in compliance with accounting principles and tax regulations. Proper classification of income, expenses, and assets enables the identification of legal tax-saving opportunities. Moreover, routine reconciliations between financial and fiscal records strengthen the reliability of the data and support the tax consultant’s ability to formulate effective strategies. Collaborating with tax consultants from the initial stages of financial statement preparation enhances the quality of tax planning and reduces the risk of errors or penalties. In conclusion, integrating accurate financial reporting with professional tax consultation significantly improves the legal effectiveness and efficiency of corporate tax planning.